Piezoelectric thin films for double electrode CMOS MEMS surface acoustic wave (SAW) resonator - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Alam, A. H. M. Zahirul; Hashim, Uda; Othman, Raihan (Springer Berlin / Heidelberg, 2015)
CMOS integration for RF-MEMS is desired to yield compact, low-power and portable devices. In this work, we illustrate the usage of double electrode CMOS SAW resonators using both ZnO and AlN as its piezoelectric material. Double electrode transducers were chosen, as they are better at suppressing undesired acoustic reflections compared to single electrodes. The structure and dimension of the device is based on 0.35 μm CMOS process where the IDTs are fabricated using standard CMOS fabrication process. 2D Finite element modeling of the CMOS SAW resonator using COMSOL Multiphysics® is presented. Two-step eigenfrequency and frequency domain analyses were performed. The acoustic velocities generated are 3,925 and 5,953 m/s for ZnO and AlN CMOS SAW resonator respectively. Higher acoustic displacement and surface potential were observed in ZnO compared to AlN. It can be concluded that ZnO thin films have higher electromechanical coupling coefficients and are more efficient than AlN thin films.